Tackling trade-offs in the nexus of water, energy and food - Pittock, J.; Or, S.; Stevens, L.; Aheeyar, Mohamed M. M.; Smith, M. (Elsevier, 2015)
We explore processes that enable effective policies and practices for managing the links between water, energy, and food. Three case studies are assessed at different scales in the Mekong River basin, Sri Lanka and Zimbabwe. We find that there are considerable opportunities for improving outcomes for sustainable development by finding solutions that accommodate multiple objectives in the nexus. These include making data more publicly available, commissioning independent experts to advise on contested issues, engaging under-represented stakeholders in decision-making, sharing benefits, exploring different perspectives in forums where alternative development options can be tested and engaging decision-makers at different scales.